ROLE OF STAPHYLOCOCCUS HAEMOLYTICUS AND ANTIBIOTIC RESISTANCE IN VAGINAL AEROBIC VAGINITIS: https://doi.org/10.5281/zenodo.15240215 - Ermatova , H.Y.; Urmonalieva , Sh.U.; Abduvohidova , Y.; Gulomov , J. I.; Abdunabiev , A. M.; Sohibnazarova, Kh.A. (International scientific and practical conference, 2025)
Staphylococcus haemolyticus (S. haemolyticus) is one of the predominant bacterial species found in aerobic vaginitis (AV) microbiota. This bacterium has a higher level of antibiotic resistance than coagulase-negative staphylococci, which makes it a clinically important pathogen. Studies have shown that S. haemolyticus has the ability to transfer antibiotic resistance genes to other staphylococcal species, which complicates antibiotic therapy. In addition, this bacterium is not only associated with aerobic vaginitis, but can also cause severe infections such as meningitis, prostatitis, urinary tract infections, and otitis media, especially in immunocompromised patients. In women, S. haemolyticus has been shown to cause dysbiosis of the vaginal microbiota, increase inflammatory processes, and promote the growth of other pathogenic microorganisms. This study evaluated the antibiotic susceptibility of S. haemolyticus strains associated with aerobic vaginitis and investigated their pharmacological properties. The results obtained confirm the high level of antibiotic resistance of S. haemolyticus and its clinical significance, and are of great importance in the development of AV treatment strategies.